Demographic evidence that development is not compatible with sustainability in semi‐urban freshwater turtles - Auge, A.‐C.; Blouin‐Demers, G.; Hasler, C. T.; Murray, D. L. (Animal conservation, 2024)
Balancing urban development with environmental sustainability is a major challenge that is increasingly recognized in planning decisions. Urban development proposals are often approved with the expectation that deleterious impacts on native species will be constrained, but this assumption is rarely tested over sufficient timelines to confirm its validity for long‐lived, at‐risk species. We tracked changes in Blanding's turtle (Emydoidea blandingii) habitat availability and demography over 10 years near Ottawa, ON, Canada, to determine whether urban development and associated mitigation measures were sufficient to ensure long‐term population persistence. Suitable turtle habitat declined by 10% during the study, and wetland corridors were essentially lost. Habitat loss coincided with a marked reduction in adult turtle apparent survival, resulting in a 70% decline in population size. Adult females experienced the greatest decline, and despite wildlife fencing and culvert placement as conditions of project approval, turtle road mortality likely was the primary cause of the decline. Deterministic population viability analysis revealed that ~4 adult female road mortalities (of an initial 56 females) per year produced a comparable decline to that observed in our population estimates; at this rate, the population will likely breach its quasi‐extinction threshold (4 females) in under a decade. Accordingly, we infer that in our study area, approved urban development was not compatible with at‐risk turtle population viability. Our findings imply that urban development approval conditions, even when conducted in the context of seemingly robust species‐at‐risk protection, can be inadequate to ensure sustainability. We contend that if environmental sustainability is to be prioritized, urban development projects in areas occupied by at‐risk species must be subject to more stringent oversight during the planning, approval and implementation phases. Balancing urban development with environmental sustainability is a major challenge in planning decisions, especially with regards to long‐lived, at‐risk species. We tracked changes in Blanding's turtle habitat and demography over 10 years near Ottawa, ON, Canada, to determine the impacts of urban development on long‐term population persistence. Suitable turtle habitat declined by 10% during the study, which coincided with a marked reduction in adult turtle apparent survival, resulting in a 70% decline in population size. Adult females experienced the greatest decline, and despite mitigation measures to offset negative impacts, turtle road mortality likely was the primary cause of the decline. Population viability analysis revealed that four adult female road mortalities per year could have led to this decline; at his rate, the population will likely breach its quasi‐extinction threshold in under a decade. We infer that in our study area, urban development was not compatible with turtle population viability.